2010
DOI: 10.2495/si100041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of deficit irrigation and mulch on water use and yield of drip irrigated onions

Abstract: A field experiment was conducted at Melkassa Agricultural Research Centre in the Central Rift Valley of Ethiopia (located at latitude 8° 24'N, longitude 39° 21'E and altitude 1,550 m above sea level) during the 2008/2009 dry season to study the 'Effect of deficit irrigation and different mulch covers on water use and yield of drip irrigated onion (Allium Cepa L., cultivar: Bombay Red)'. A drip irrigation system with 144 laterals was used for the experiment. Two factors, namely deficit irrigation at four levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 2 publications
1
3
1
Order By: Relevance
“…In this study, the irrigation water productivity (IWP) values for onion crops ranged from 2.18 to 3.42 kg m −3 , which were found to be considerably lower than those reported by Ramalan et al [61] in Ethiopia (9.16-15.94 kg m −3 ) and Igbadun et al [29] in Nigeria (3.8-5.2 kg m −3 ). However, the findings of this study also indicated that the water productivity of onion crops is comparable to that reported by Nyath et al [62] for traditional vegetables (1.29 kg m −3 ) and alien vegetables (1.37 kg m −3 ).…”
Section: Discussioncontrasting
confidence: 65%
“…In this study, the irrigation water productivity (IWP) values for onion crops ranged from 2.18 to 3.42 kg m −3 , which were found to be considerably lower than those reported by Ramalan et al [61] in Ethiopia (9.16-15.94 kg m −3 ) and Igbadun et al [29] in Nigeria (3.8-5.2 kg m −3 ). However, the findings of this study also indicated that the water productivity of onion crops is comparable to that reported by Nyath et al [62] for traditional vegetables (1.29 kg m −3 ) and alien vegetables (1.37 kg m −3 ).…”
Section: Discussioncontrasting
confidence: 65%
“…Bandeira et al (2013) also obtained highest marketable yield of onion bulbs applying water depth corresponding to 100% ETc, compared with 75% ETc, performing irrigation management with Class A pan and without using mulch. Similar effect of different irrigation depths on onion bulb yield have also been observed by Olalla et al (2004), Enciso et al (2009), Ramalan et al (2010) and Igbadun et al (2012). Kumar et al (2007) demonstrated that a greater water comfort to the onion crop is obtained when the soil is maintained close to field capacity (100% ETc), promoting …”
Section: Methodssupporting
confidence: 56%
“…Igbadun and Oiganji (2012), Ramalan, Nega, and Oyebode (2010) and Ribeiro et al (2016) observed that irrigation depths had similar effects on the yield of onion bulbs. The reduction in irrigation depth of 36% (321 to 204 mm) in 2014 and of 37% (444 to 278 mm) in 2015 resulted in losses of 29, 30, 33, and 11% and 38, 38, 34, and 17% in TY, MBFW, MBDW and MBD, respectively, in each year.…”
Section: Resultsmentioning
confidence: 94%